Agroforestry in the Indian Tropics - Kumar, B. Mohan (Indian Journal of Agroforestry, 2020)
Tropical regions of India are characterised by diverse land use systems that integrate woody perennials with other life forms. A constant radiation surplus and the general thermic uniformity, typical of these zones probably sustain such diversity in land use practices. Social, economic and ecological reasons for the popularity of agroforestry in the tropics, system components and the functional dynamics of important humid tropical agroforestry practices in the peninsular Indian context are described.